2007
DOI: 10.1002/jcb.21617
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of immortal liver progenitor cells into pancreatic endocrine progenitor cells by persistent expression of Pdx‐1

Abstract: The conversion of expandable liver progenitor cells into pancreatic beta cells would provide a renewable cell source for diabetes cell therapy. Previously, we reported the establishment of liver epithelial progenitor cells (LEPCs). In this work, LEPCs were modified into EGFP/Pdx-1 LEPCs, cells with stable expression of both Pdx-1 and EGFP. Unlike previous work, with persistent expression of Pdx-1, EGFP/Pdx-1 LEPCs acquired the phenotype of pancreatic endocrine progenitor cells rather than giving rise to insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…PDX1 overexpression experiments provide some evidence that this factor can partially engage the pancreatic program while conversely suppressing endogenous liver genes. In studies with primary rodent hepatocytes or liver epithelial cells, Alb levels were variably downregulated by overexpressing PDX1 or PDX1-VP16 ( Fodor et al., 2007; Jin et al., 2008; Meivar-Levy et al., 2007; Yamada et al., 2006 ). Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…PDX1 overexpression experiments provide some evidence that this factor can partially engage the pancreatic program while conversely suppressing endogenous liver genes. In studies with primary rodent hepatocytes or liver epithelial cells, Alb levels were variably downregulated by overexpressing PDX1 or PDX1-VP16 ( Fodor et al., 2007; Jin et al., 2008; Meivar-Levy et al., 2007; Yamada et al., 2006 ). Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that distant relationships between cells can be deduced by following consecutive neighborhood links. For example, the differentiation route of liver progenitor cells to pancreatic beta cells, which is already reported (34), is determined by successively following the links from ‘liver progenitor cell (stem cell ID:802, Figure 4a top) to hepatocyte (differentiated cell ID:160032, Figure 4a bottom)’ and from ‘hepatocyte to pancreatic beta cell (differentiated cell ID:150041, Figure 4a right)’.…”
Section: Applications Of Cellpediamentioning
confidence: 89%
“…Ferber’s group reported that in vivo transduction of Ad-PDX1 into the mouse liver results in the production of substantial amounts of insulin [31] . Extensive research has been undertaken to investigate the in vitro transdifferentiation of adult liver cells from rodents [3] , [23] , [24] , [32] , [33] and humans [25] , [34] using virus-mediated gene delivery systems as a potential source of β-cells for transplantation into patients with type 1 diabetes. Although these cells transdifferentiate to express insulin, they are clearly far from true pancreatic β-cells, and major obstacles remain to be overcome.…”
Section: Discussionmentioning
confidence: 99%